2018
DOI: 10.1016/j.foodres.2017.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of physical and rheological properties of grape juice using different temperatures and concentrations. Part II: Merlot

Abstract: The effect of the temperature and concentration on rheological behavior of Merlot juice concentrates was assessed using a rheometer over a wide range of temperature (1-66°C) and concentrations (13.6-45.0Brix) at shear rates of 0.84-212.1 1/s. The Ostwald-De Waele was the best rheological model fitted the data (R=0.99967 and relative error=7.99%). The consistency levels were significantly reduced with the increase of temperature and increased with the increase of the concentrations, ranging from 0.1766 (13.6Bri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 26 publications
4
10
0
Order By: Relevance
“…All the values of flow behavior index (n) were less than 1 which proved the shear-thinning and non-Newtonian behavior of the red wine samples (Trávníček et al, 2016). Our results concerning the non-Newtonian pseudoplastic behavior of red wine samples agreed with the previous studies (De Castilhos et al, 2018). Higher K value indicated the higher apparent viscosity.…”
Section: Rheological Properties Of Red Wines From Xixia King Chateausupporting
confidence: 90%
“…All the values of flow behavior index (n) were less than 1 which proved the shear-thinning and non-Newtonian behavior of the red wine samples (Trávníček et al, 2016). Our results concerning the non-Newtonian pseudoplastic behavior of red wine samples agreed with the previous studies (De Castilhos et al, 2018). Higher K value indicated the higher apparent viscosity.…”
Section: Rheological Properties Of Red Wines From Xixia King Chateausupporting
confidence: 90%
“…Regarding the temperature, Figure 2(d)-(f) also showed that specific heat slightly increases with increasing temperature. This same trend was noticed for Cabernet Sauvignon grape juice (Castilhos et al, 2017), Merlot grape juice (Castilhos et al, 2018), juices and syrups from a noncentrifugal sugar cane production process (Alarcón et al, 2020), meat extract (Polachini, Betiol, Bastos, Telis, & Telis-Romero, 2017), pequi pulp (Souza, Queiroz, Figueirêdo, Santos, & Lemos, 2016) and papaya puree (Tansakul, Kantrong, Saengrayup, & Sura, 2012). So, it could be assumed that diluted solutions demand more energy to increase the temperature than concentrated solutions with the same mass.…”
Section: Specific Heat (C P )supporting
confidence: 62%
“…The experimental data of sucrose, glucose and fructose solutions were very similar (maximum deviation of 3%) to that observed by Darros-Barbosa et al 2003 On the other hand, the same Figure (2a-c) showed that density was inversely proportional to the temperature: it increased as the temperature decreased. The same behavior is observed for different products, such as grape juice Merlot (Castilhos et al, 2018), meat extract (Polachini et al, 2016), Malay Rose apple pulp (Fontan et al, 2018), juices and syrups from a noncentrifugal sugar cane production process (Alarcón, Orjuela, Narvaéz, & Camacho, 2020) and…”
Section: Mathematical Modelingmentioning
confidence: 54%
See 1 more Smart Citation
“…This behavior is rationed with the food processing conditions, whether thermal and non-thermal processes, affect the natural structure and the composition of food powders; the structure of foods can have a profound influence on its nutritional value, rheology and functional attributes [24]. The rheological behavior of a fluid is influenced by several factors, mainly the intermolecular forces and the water-solute interaction which limit the movement of the particles at a molecular level [25]. Changes in the temperature and concentration can lead to significant changes in the intermolecular forces [26].…”
Section: Rheological Analysismentioning
confidence: 99%